GOTTSCHALL, Jonathan. The story telling animal: how stories make us human. Boston/New York: Houghton Mifflin Harcourt, 2012. 248 p. - Lima, Marcus Assis (Aletria: Revista de Estudos de Literatura, 2014)
Resenha de The story telling animal: how stories make us human, de Jonathan Gottschall.